2006
DOI: 10.1093/jn/136.9.2421
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Qualitative Study of Infant-Feeding Decision Making and Practices among HIV-Positive Women in South Africa

Abstract: This study examined the challenges that HIV-positive women face at different stages of early infant feeding using a longitudinal, qualitative design. The study explored factors influencing infant-feeding decision-making and behavior of HIV-positive mothers and identified characteristics of women and their environments that contributed to success in maintaining exclusivity of their infant feeding practices. The study was undertaken at 3 sites in South Africa. Participants consisted of a purposive sample of 27 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
17

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 17 publications
4
65
1
17
Order By: Relevance
“…The studies revealed that non-adherence was common among the mothers because of challenges relating to the individual mother, the family, the community, socio-economic factors, cultural factors and health care system constraints. 11,12,13 The studies were mostly done in rural and peri-urban areas in the Western Cape, Eastern Cape and KwaZulu-Natal provinces. Doherty et al 12 reported studies at three PMTCT of HIV sites in the three provinces whereby interviews with 27 HIV-infected mothers during the postpartum period revealed that just under half of the mothers who intended breast-feeding maintained exclusivity and over two-thirds of the mothers who initiated formula feeding maintained exclusivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies revealed that non-adherence was common among the mothers because of challenges relating to the individual mother, the family, the community, socio-economic factors, cultural factors and health care system constraints. 11,12,13 The studies were mostly done in rural and peri-urban areas in the Western Cape, Eastern Cape and KwaZulu-Natal provinces. Doherty et al 12 reported studies at three PMTCT of HIV sites in the three provinces whereby interviews with 27 HIV-infected mothers during the postpartum period revealed that just under half of the mothers who intended breast-feeding maintained exclusivity and over two-thirds of the mothers who initiated formula feeding maintained exclusivity.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,13 The studies were mostly done in rural and peri-urban areas in the Western Cape, Eastern Cape and KwaZulu-Natal provinces. Doherty et al 12 reported studies at three PMTCT of HIV sites in the three provinces whereby interviews with 27 HIV-infected mothers during the postpartum period revealed that just under half of the mothers who intended breast-feeding maintained exclusivity and over two-thirds of the mothers who initiated formula feeding maintained exclusivity. Bland et al 13 found among 1 253 HIV-infected mothers in KwaZulu Natal that 78% of mothers who intended EBF were able to adhere in the first postnatal week, and 42% who intended ERF were able to adhere.…”
Section: Discussionmentioning
confidence: 99%
“…13 24 Uma das fontes de suporte social instrumental mencionada [16][17][18][19] são os PPTVs, os quais utilizaram uma abordagem centrada na família e dessa forma, contribuíram para divulgação do estado sorológico, e para a adesão aos antirretrovirais. Nesta perspectiva 13,19,23 destaca-se a importância da participação de mulheres em PPTV, as quais realizaram a divulgação de seu diagnóstico e receberam apoio dos seus familiares.…”
Section: Discussão Fontes E As Repercussões Do Suporte Social Instrumunclassified
“…Participação em programas de prevenção 13,16,[18][19][20][23][24][25][26][27][28] Acolhimento da equipe de saúde 11,16,21,24 Educação em saúde 20 Conforto das condições de saúde 24 Divulgação do estado sorológico [16][17][18][19] Aderir às medidas de profilaxia da TV 11,[16][17][18][19] Repercussões na saúde sexual 13 Deus e a fé 15,24,27 Divulgação do estado sorológico 29 Motivação para aceitar o diagnóstico e o tratamento 24 repercussões na saúde sexual: consideraram-se com maior capacidade para negociar o planejamento familiar, além do uso de preservativo, e solicitar ao companheiro que realizasse o teste de anticorpos do HIV.…”
Section: Suporte Instrumentalunclassified
“…Its application in the field of health research remains, however, limited. QLR has been used to explore "the prospect of dying; journeys to the diagnosis of cancer and living with haemodialysis" [40, page 2], to explore experiences of symptoms in cancer patients [40] and in people living with HIV [25,[145][146][147][148][149]]. The latter is described in more detail.…”
Section: Qualitative Longitudinal Research Methodologymentioning
confidence: 99%